Analysis of Factors Influencing Inseminator Performance Towards Increasing Beef Cattle Production in Deli Serdang Regency - Ismail, Ismail; Martial, Tri; Karo-Karo Sitepu, Rasidin (Journal of Agriculture, 2024)
Deli Serdang Regency is one of the key beef cattle production centers in North Sumatra, playing a crucial role in efforts to achieve self-sufficiency in meat production at both the provincial and national levels. However, in recent years, the population and production of beef cattle in this region have fluctuated, while the demand for beef remains unmet. Therefore, this study aims to identify the factors influencing the performance of inseminators in improving beef cattle production in Deli Serdang Regency. This research employs a non-random sampling method using judgment sampling techniques. The sample consists of all inseminators from the Department of Agriculture and Livestock of Deli Serdang, totaling 42 respondents. The collected data were analyzed using the SEM method with the assistance of SmartPLS4 software. The results indicate that variables such as rewards, leadership, communication, and knowledge have a positive but statistically insignificant impact on inseminator performance (P Value > 0.05). Meanwhile, skills have a positive and significant influence on inseminator performance (P Value < 0.05). Indirect testing reveals that rewards, leadership, and communication influence motivation but are not significant. Similarly, knowledge affects ability but is also not significant. However, skills have a significant impact on inseminator performance. Between 2018 and 2022, the beef cattle population in Deli Serdang Regency increased by 1.44%, reaching 102,985 heads. Conversely, beef production declined by -1.27%, with a total production of 2,040,172 tons.